2003
DOI: 10.1080/0897719031000094921
|View full text |Cite
|
Sign up to set email alerts
|

New Advances on Prostate Carcinogenesis and Therapies: Involvement of EGF-EGFR Transduction System

Abstract: The prostate cancers (PCs) are among the major causes of death because therapeutic treatments are not effective against advanced and metastatic forms of this cellular hyperproliferative disorder. In fact, although androgen-deprivation therapies permit to cure localized PC forms, the metastatic PC cells have acquired multiple functional features that confer to them resistance to ionizing radiations and anticarcinogenic drugs currently used in therapy. The present review describes last advances on molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
70
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 103 publications
1
70
0
Order By: Relevance
“…In this manner, neuroendocrine cells may activate an alternative antiapoptotic mechanism that can support tumor growth in the presence of PI3K and EGFR inhibitors. Reports on synergism between inhibitors of PKA and EGFR kinases in prostate cells and colon tumor xenografts provide circumstantial evidence that support the significance of interaction between EGFR and PKA signaling (68,69). It remains to be seen if BAD phosphorylation forms the basis for this synergism, as it was recently demonstrated for inducible expression of PTEN and EGFR inhibitor in breast cancer xenografts (59).…”
Section: Discussionmentioning
confidence: 99%
“…In this manner, neuroendocrine cells may activate an alternative antiapoptotic mechanism that can support tumor growth in the presence of PI3K and EGFR inhibitors. Reports on synergism between inhibitors of PKA and EGFR kinases in prostate cells and colon tumor xenografts provide circumstantial evidence that support the significance of interaction between EGFR and PKA signaling (68,69). It remains to be seen if BAD phosphorylation forms the basis for this synergism, as it was recently demonstrated for inducible expression of PTEN and EGFR inhibitor in breast cancer xenografts (59).…”
Section: Discussionmentioning
confidence: 99%
“…Activated EGFR may induce distinct mitotic cascades, including the MAPK, PI3K/Akt, Shc, NF-κB and phospholipase Cg signalling pathways, which stimulate the proliferation, survival, motility and invasiveness of prostate cancer cells [29][30][31][32]. Elevated Akt activity may have a profound role in the progression of human prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…24,26 Additionally, the epidermal growth factor receptor (EGFR) and its ligands, epidermal growth factor (EGF) and transforming growth factor-a (TGF-a), which assume an important role for normal prostate development, [27][28][29][30] are also overexpressed during the progression of benign, localized and metastatic forms of PC. [31][32][33][34] The upregulated activation of EGFR signaling appears notably to contribute to the sustained cell proliferation, survival and invasion of PC epithelial cells. 27,29,[31][32][33]35,36 It has also been reported that the blockade of either HH or EGF-EGFR signaling, by using a selective SMO or EGFR inhibitor, such as cyclopamine and gefitinib (also known as Iressa or ZD1839), respectively, leads to the growth inhibition and apoptotic death of many cancer cell types, including prostate tumor epithelial cells in vivo and in vitro.…”
mentioning
confidence: 99%